The Fourth Moment in Luby’s Distribution - Dubhashi, Devdatt P.; Pantziou, Grammati E.; Spirakis, Paul G.; Zaroliagis, Christos D. (BRICS Report Series, 1995)
Luby[10] proposed a way to derandomize randomized computations which is based on the construction of a small probability space whose elements are 3-wise independent. In this paper we prove some new properties of Luby’s space. More precisely, we analyze the fourth moment and prove an interesting technical property which helps to understand better Luby’s distribution. As an application, we study the behavior of random edge cuts in a weighted graph. Keywords: Fourth moment, full independence, k-wise independence, derandomization.